Finite element modeling of elastohydrodynamic lubrication problems / Wassim Habchi. - Habchi, Wassim, 1982- (Wiley, 2018)
This title covers the latest developments in modelling elastohydrodynamic lubrication (EHL) problems using the finite element method (FEM). The comprehensive guide introduces readers to a powerful technology being used today in the modelling of elastohydrodynamic lubrication (EHL) problems.